A comparative study on the quality and safety perception of public open spaces (POS) between low-cost housing and high-end residences in Davao City - Serquin?a, JC Waldo J.
The study sought to compare the quality and safety perception of public open spaces between low-cost housing and high-end residences in Davao City and specifically aims to evaluate their differences and similarities, as well as the strengths and weaknesses of existing conditions. The Community Park Audit Tool (CPAT) was the data gathering tool of choice, assessing the public open spaces within four subdivisions through four criteria: Park Information; Access and Surrounding Neighborhood, Activity Areas; and Quality and Safety. Results reveal that low-cost public open spaces cater residents extensively through a diverse catchment hierarchy; however, this resulted in lack of oversight and maintenance on local open spaces, leading to poor quality and safety. On the other hand, high-end public open spaces cater residents intensively through the use of few, highly maintained public open spaces; however, this restricted catchment hierarchy, resulting in accessibility issues, especially with distance. Study results recommend that percentage of allocated area for public open spaces be kept constant within multiphase subdivisions regardless of housing density to encourage diversity of catchment area, in conjunction with consistent provision of sidewalks, encouragement of alternate modes of circulation (e.g. bike lanes); and regular maintenance to improve quality and safety perception of public open spaces across housing markets."